Acute decompensated heart failure (ADHF) : a comprehensive contemporary review on preventing early readmissions and postdischarge death - Rocha, Bruno Miguel Lopes (2017)
Trabalho Final do Curso de Mestrado Integrado em Medicina, Faculdade de Medicina, Universidade de Lisboa, 2016